Computational microstructure modeling to estimate progressive moisture damage behavior of asphaltic paving mixtures. (16th July 2012) - Ban, Hoki; Kim, Yong‐Rak; Rhee, Suk‐Keun
SUMMARY This paper presents a computational microstructure model to estimate the progressive moisture damage of multiphase asphaltic paving mixtures. Moisture damage because of water transport is incorporated with mechanical loading through a finite element method. To simulate nonlinear damage evolution in the mixtures, the model includes Fickian moisture diffusion, a cohesive zone model to simulate the gradual fracture process, and a degradation characteristic function to represent the reduction of material properties because of moisture infiltration. With the model developed, various parametric analyses are conducted to investigate how each model parameter affects the material‐specific moisture damage mechanism and damage resistance potential of the mixtures. Analysis results clearly demonstrate the significance of physical and mechanical properties of mixture components and geometric characteristics of microstructure for the better design of asphaltic paving mixtures and roadway structures. Copyright © 2012 John Wiley & Sons, Ltd.